2003
DOI: 10.1016/s0014-5793(02)03882-6
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate stimulates cortisol secretion

Abstract: We show here for the ¢rst time that sphingosine-1-phosphate (Sph-1-P) stimulates cortisol secretion in zona fasciculata cells of bovine adrenal glands. This e¡ect was dependent upon protein kinase C (PKC) and extracellular Ca 2+ , and was inhibited by pertussis toxin. Sph-1-P activated phospholipase D (PLD) through a pertussis toxin-sensitive mechanism, also involving extracellular Ca 2+ and PKC. Primary alcohols, which attenuate formation of phosphatidic acid (the product of PLD), and cell-permeable ceramides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 38 publications
3
39
0
1
Order By: Relevance
“…Both of these pathways are essential for many of the biological functions that are regulated by S1P (6,11,12). In particular, PI3K and ERK have been implicated in the stimulation of steroidogenesis by different agonists (3,(13)(14)(15)(16)(17)(18), and we found that S1P is also a potent stimulator of cortisol secretion (19).…”
mentioning
confidence: 52%
“…Both of these pathways are essential for many of the biological functions that are regulated by S1P (6,11,12). In particular, PI3K and ERK have been implicated in the stimulation of steroidogenesis by different agonists (3,(13)(14)(15)(16)(17)(18), and we found that S1P is also a potent stimulator of cortisol secretion (19).…”
mentioning
confidence: 52%
“…Others have shown that S1P stimulates cortisol secretion in zona fasciculata bovine adrenal cells in a PKC and Ca 2+ -dependent manner (Rabano et al, 2003). In addition to stimulating cortisol There have been many other reports of the stimulatory and inhibitory effects of bioactive sphingolipids on steroid hormone biosynthesis in both gonadal and adrenal cell lines (Budnick et al, 1999;Degnan et al, 1996;Kwun et al, 1999;McClellan et al, 1997;Meroni et al, 2000;Porn et al, 1991;Rabano et al, 2003;Santana et al, 1996). Increased ceramide levels stimulate progesterone synthesis in both MA-10 murine Leydig cells (Kwun et al, 1999) and JEG-3 human choriocarcinoma cells (McClellan et al, 1997).…”
Section: Bioactive Sphingolipids In Steroidogenesismentioning
confidence: 97%
“…S1P activates a cascade of events culminating in the binding of the sterol regulatory element binding protein-1 (SREBP-1) to the promoter of CYP17, the activation of transcription, and increased cortisol biosynthesis. Others have shown that S1P stimulates cortisol secretion in zona fasciculata bovine adrenal cells in a PKC and Ca 2+ -dependent manner (Rabano et al, 2003). In addition to stimulating cortisol secretion, S1P has been recently found to increase aldosterone production via a protein kinase C and phospholipase D-dependent pathway (Brizuela et al, 2006).…”
Section: Bioactive Sphingolipids In Steroidogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Among the possible effectors of adrenal steroidogenesis, increased levels of fatty acids or other lipid metabolites, within the adrenal cortex, could be involved in the dysregulation of basal corticosterone production (Sarel & Widmaier 1995, Rabano et al 2003. In addition, the regulation of steroidogenesis by adipocyte secretory products generated by fat cells detected in close contact with steroidogenic cells has also been shown (Ehrhart-Bornstein et al 2003).…”
Section: Weeks Of Treatmentmentioning
confidence: 99%